Dragon's dream - Dean, Roger, 1944-.; Shields, Amanda (New York : Collins Design, 2008)
Includes "a panoramic dreamscape of original paitnings; album covers, logos, and stage designs for bands ... virtual worlds, characters, and logos for computer games companies ... and concepts and designs for both opera and animated movies."--jacket flap.
Fakulti Teknologi Kreatif Dan Warisan.
Includes index.
Keywords: Animated films -- Illustrations -- Case studies; Fantasy in art; Video games -- Design -- Illustrations